The Effect of Maturity Level and Size on The Viability of Cinnamon Seeds at Different Storage Time Periods (Cinnamomum burmanii. L) - Eliza Mayura; Herwita Idris; Melati Melati (Journal of Applied Agricultural Science and Technology, 2023)
Cinnamomum burmanii L, a cinnamon plant developed in Indonesia, requires high-quality seeds, yet plant propagation faces challenges due to limited access to quality seeds at the appropriate time. This study aimed to determine the viability of cinnamon seeds from the level of maturity of the seeds and size. The experimental design used in this study was a randomized completed block design with a factorial pattern, with the first-factor treatment being the maturity level of the seeds, namely: 1) K1 (purple) and 2) K2 (purplish-green). The second factor was the size of the seeds, namely: 1) U1 (large size) and 2) U2 (small size) at different storage times, namely at the beginning of storage, 4,7, and 10 days after storage. The observed variables included water and carbohydrate content, germination, and seed vegetative growth (seed height, number of leaves, leaf length, leaf width, roots, and root length). The results showed that the interaction of cinnamon seeds with large size and purple maturity level had the highest viability in all storage periods. Germination reaches 70%, carbohydrate content 15.28%, and moisture content 10.51% ten days after storage.